PERAN AMIL ZAKAT DALAM MENGOPTIMALKAN ZAKAT PRODUKTIF: STUDI ANALISIS BADAN AMIL ZAKAT DAERAH (BAZDA) KOTA BEKASI - Setiadi, Muhammad Romi; Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
The purpose of this study is (1) to determine the role of Zakat Regional Management Board (BAZDA) Kota Bekasi in optimizing the productive zakat. (2) todetermine the constraints faced by the Zakat Regional Management Board (BAZDA) Kota Bekasi in optimizing the productive zakat. This study used qualitative methods naturalistic sources of primary data obtained directly through interviews and questionnaires to zakat and mustahiq (entitled to receive zakat). Primary datasupported secondary data in the form of books, articles, and others that are relevant to this study. The conclusion of this study that the role of Bekasi BAZDA, namely giving counseling to the community, to provide capital assistance or revolving funds for mustahiq (entitled to receive zakat), to provide financial assistance consumptive, provides tuition assistance to those who can not afford, and helping people around for lost items/money. BAZDA constraints in carrying out its role, among others, the difficulty of monitoring to the mustahiq and is still a lack of human resources in the field of supervision.